METTL3 blocked the progression of diabetic retinopathy through m6A-modified SOX2 - Chen Xiujuan; Ling Qipeng; Xu Jie; Ye Yunyao; Dong Lili (Open Medicine)
We aimed to explore the regulatory effects of methyltransferase-like 3 (METTL3) on diabetic retinopathy (DR) by regulating the m6A modification of SOX2 mRNA and elucidating the underlying molecular mechanism. The DR model was established by stimulating human retinal endothelial cells (HRECs) with high glucose (HG). METTL3, insulin-like growth factor 2 binding protein 2 (IGF2BP2), and SOX2 levels in the sera of patients with DR and HRECs were determined using qRT-PCR and western blotting. Moreover, the interactions between SOX2 and METTL3 or IGF2BP2 were confirmed using RNA-binding protein immunoprecipitation (RIP) experiments. Furthermore, HRECs proliferation and apoptosis were determined using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and flow cytometry, respectively. The protein level of cleaved-caspase3 and caspase3 in HRECs were evaluated using western blotting. The results indicated that the expression of METTL3, IGF2BP2, and SOX2 was notably decreased in the serum of patients with DR, as well as in HRECs under HGs. RIP further verified the relationship between METTL3 and SOX2 mRNA expression. HG treatment inhibited HREC viability, increased apoptosis, and enhanced cleaved-caspase3 expression and cleaved-caspase3/caspase3 ratio. Upregulation of METTL3 significantly restored the effects of HG, whereas SOX2 knockdown partially reversed the regulatory effects of METTL3 on HRECs. In summary, METTL3 blocks the progression of DR by regulating m6A modification on SOX2 mRNA.